Scientific-Methodological Foundations of Developing Schoolchildren's Interest in Physical Education and Public Sports (In the Case of High School Girls) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
This article examines the scientific-methodological foundations for developing schoolchildren's interest in physical education and public sports, specifically focusing on high school girls. It explores various strategies and approaches that can be employed to foster girls' engagement and passion for physical activity. The article emphasizes the importance of creating inclusive and supportive environments, providing mentorship opportunities, integrating technology, and collaborating with community partners. It also highlights the significance of addressing gender stereotypes, promoting holistic well-being, and offering diverse sports experiences. The findings of this study contribute to the development of effective practices in physical education and public sports programs for high school girls.